THE IMPACT OF CAPITAL ADEQUACY RATIO, CAPITAL STRUCTURE, NON-PERFORMING LOAN, AND RETURN ON ASSETS TOWARDS FIRM VALUE OF BANKING COMPANIES LISTED IN INDONESIA STOCK EXCHANGE - Geoffry Japin; Ciptawan Ciptawan (Proceeding National Conference Business, Management, and Accounting (NCBMA), 2022)
This study aims to determine the impact of the Capital Adequacy Ratio, Capital Structure, Non-Performing Loan, and Return on Assets partially and simultaneously on firm value. The sample of this study is banking companies listed on the Indonesia Stock Exchange starting from year 2017 to 2020 using the purposive sampling method. There are 27 banking companies that meet the criteria as research samples. The data that has been collected is then processed using the SPSS 26.0 application and tested with normality, heteroscedasticity, multicollinearity, and linearity tests. Furthermore the data is tested further with multiple linear regression testing, the coefficient of determination and continued with hypothesis testing consisting of T test and F test. The results of this study indicate that the Capital Adequacy Ratio partially has an insignificant effect on Firm Value, Capital Structure partially has a significant effect on firm value, Non-Performing Loan partially has a significant effect on firm value, and Return on Assets partially has a significant effect on Firm Value. Simultaneously, the variables: Capital Adequacy Ratio, Capital Structure, Non-Performing Loan, and Return on Assets have a significant effect on firm value.BAHASA INDONESIA ABSTRACTPenelitian ini bertujuan untuk mengetahui Pengaruh Capital Adequacy Ratio, Capital Structure, Non-Performing Loan, and Return on Assets secara parsial dan simultan terhadap Nilai Perusahaan. Sampel penelitian ini adalah perusahaan perbankan yang tercatat di Bursa Efek Indonesia dimulai dari tahun 2017 hingga 2020 dengan menggunakan metode purposive sampling. Terdapat 27 perusahaan perbankan yang memenuhi kriteria sebagai sampel penelitian. Data yang telah terkumpul selanjutnya diolah menggunakan aplikasi SPSS 26.0 dan diuji dengan uji normalitas, heteroskedastisitas, multikolinearitas, dan linieritas. Selanjutnya, dilakukan pengujian regresi linier berganda, koefisien determinasi dan dilanjutkan dengan pengujian hipotesis yang terdiri dari uji T dan uji F. Hasil penelitian ini menunjukkan bahwa Capital Adequacy Ratio secara parsial tidak berpengaruh signifikan terhadap Nilai Perusahaan, Capital Structure secara parsial berpengaruh signifikan terhadap nilai perusahaan, Non-Performing Loan secara parsial berpengaruh signifikan terhadap nilai perusahaan, and Return on Assets secara parsial berpengaruh signifikan terhadap Nilai Perusahaan. Secara simultan, variable Capital Adequacy Ratio, Capital Structure, Non-Performing Loan, and Return on Assets berpengaruh signifikan terhadap Nilai Perusahaan.